Organic cation transporter Octn1-mediated uptake of food-derived antioxidant ergothioneine into infiltrating macrophages during intestinal inflammation in mice. Issue 3 (June 2015) - Shimizu, Takuya; Masuo, Yusuke; Takahashi, Saki; Nakamichi, Noritaka; Kato, Yukio
Abstract: OCTN1/SLC22A4 is expressed on apical membranes of small intestine, and is involved in gastrointestinal absorption of its substrates, including the food-derived antioxidant ergothioneine (ERGO). ERGO concentration in circulating blood of patients with inflammatory bowel disease (Crohn's disease) is lower than that in healthy volunteers; thus, circulating ERGO is a potential diagnostic marker, although the mechanisms underlying low ERGO concentration in patients are unknown. Here, we focused on intestinal macrophages, which infiltrate sites of inflammation, and examined possible first-pass uptake of ERGO by macrophages. ERGO concentration in blood was lower in mice with dextran sodium sulfate (DSS)-induced colitis than in controls. On the other hand, expression of octn1 gene product and ERGO concentration in intestinal tissues of DSS-treated mice were higher than in controls. Interestingly, lamina propria mononuclear cells (LPMCs) isolated from DSS-treated mice contained ERGO and showed [ 3 H]ERGO uptake and Octn1 expression, whereas ERGO was undetectable in LPMCs of control mice. Functional expression of OCTN1 was also confirmed in LPS-stimulated human macrophage-like cell line, THP-1. In conclusion, OCTN1 is functionally expressed on activated intestinal macrophages, and ERGO uptake into these immune cells could contribute at least in part to the altered disposition of ERGO in intestinal inflammation.